ONLINE GAME QUIZ “KAHOOT” IN TEACHING ENGLISH FOR STUDENTS OF SMP MUHAMMADIYAH YOGYAKARTA - Oktaria, Annafi Annanda; Rohmayadevi, Laksmita; Murwantono, Didik (PROJECT (Professional Journal of English Education), 2021)
Gamification is gaining momentum together with technology-infused training as an advancement to inspire and engage students in their learning process. The correlation between game play and increased motivation and interaction is shown by strong evidence. More and more games of learning appear, offering a promise to help learning a language. This research was designed in descriptive qualitative research; data was collected by short questions to be answered on the application of Kahoot online application in English classrooms. The aim in this research to analyze motivation of the students and to enrich the dynamics of the lessons introducing Kahoot in the English classroom in order to achieve improve the tasks related to vocabulary, aimed at defining vocabulary. The research design was qualitative research concerning phenomenological studies with a sample of 30 students of Junior High School of SMP Muhammadiyah Yogyakarta. It used an open-ended questionnaire to collect the data of the students' perceptions. Data analysis of the questionnaires was analyzed qualitatively by interview. With the media Kahoot can improve student learning achievement as evidence that the results of learning English experience a significant increase in value. It is very helpful for students in addition to understanding English subject matter.Keywords:  education, kahoot, learning, motivation, smartphone